Analisis Hukum Implementasi Undang-Undang Cipta Kerja dan Problematikanya pada PT. Dharmamulia Prima Karya - Elizabeth Devina Putri; Angelita Audria; Almira Kharisma Maharani; Daffa Arya Prayoga; Alexander Jonathan Arya Widya Pratama (CV. Ulil Albab Corp, 2022)
Undang-Undang Cipta Kerja or commonly referred to as UUCK is a law drawn up by the government that regulates several fields, one of which is the manpower sector. This law was made to make it easier for investors and entrepreneurs to invest in Indonesia. Regarding employment itself, UUCK deletes, adds, and changes several articles in the UU Ketenagakerjaan. This change, of course, resulted in a polemic for labor actors, namely employers and workers. PT Dharmamulia Prima Karya as one of the outsourcing service providers was affected by the formation of the law. In conducting the research, the author uses a normative-empirical method that looks at how a substance in the law is formed and how the law is implemented in society directly. The author will describe descriptively and thoroughly about the research results obtained.